2016
DOI: 10.1515/biol-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

Improving aeration for efficient oxygenation in sea bass sea cages. Blood, brain and gill histology

Abstract: An air diffusion based system (Airx) was developed to control the dissolved oxygen levels in aquaculture sea cages. The system was introduced and then tested for 37 days in a sea bass sea cage (aerated cage). A second sea bass sea cage, without the AirX, was used as a control. Oxygen levels were measured in both cages at the start of the trial, before the AirX system was introduced, and during the working period of the AirX system. Fish samples were collected 15 days after the AirX system was introduced and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
1
11
1
Order By: Relevance
“…Contrarily, in our analysis by flow cytometry and immuno-histochemistry, the B-cells seemed to diminish in thymus (just a trend, not statistically significant) and gut (p < 0.05) in the HO group as compared to the NO group. Recently, a study in aquaculture has revealed that the oxygen treatment of ≥70% of saturation improves the quantity and the performance of the oxygen-releasing of red blood cells; however, contrary to our findings, no histological differences were revealed in lymphocyte number [25]. In the present research, we evidenced both in flow cytometry analysis and immuno-histochemistry, a significant increment of T-cells in the organs normally enriched of lymphocytes of type "T" [18], such as thymus, gut, and gills.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrarily, in our analysis by flow cytometry and immuno-histochemistry, the B-cells seemed to diminish in thymus (just a trend, not statistically significant) and gut (p < 0.05) in the HO group as compared to the NO group. Recently, a study in aquaculture has revealed that the oxygen treatment of ≥70% of saturation improves the quantity and the performance of the oxygen-releasing of red blood cells; however, contrary to our findings, no histological differences were revealed in lymphocyte number [25]. In the present research, we evidenced both in flow cytometry analysis and immuno-histochemistry, a significant increment of T-cells in the organs normally enriched of lymphocytes of type "T" [18], such as thymus, gut, and gills.…”
Section: Discussioncontrasting
confidence: 99%
“…Immuno-histochemistry was performed as previously described [25]. Tissues were sampled from thymus, head kidney, spleen, intestine (middle segment 2-cm long, taken 3 cm caudally to opening of bile duct), and gills (portion of mucosae adherent to the gill arch, comprehensive of primary and secondary lamellae) and were fixed in Bouin's fluid for 7 h at 4 • C, dehydrated in graded alcohols at 4 • C, cleared in toluene and embedded in paraffin wax.…”
Section: Immuno-histochemistrymentioning
confidence: 99%
“…This pattern was observed for stoking density trial, but not for oxygen trial. The different variation pattern could be a result of cell volume increase instead of number (Berillis et al, ), since red blood cells swelling has been described for fish under stressful conditions (Brill et al, ). However, no significant differences were observed for red cell volume on the blood smears analysed for the present study (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…These lamellae are hollowed flap-shaped structures where an intense blood flow runs in-between supportive cells called pillar cells. A typical branchial epithelium is mainly composed of pavement cells in-between which reside chloride cells (also called mitochondria-rich cells), mucous cells and neuroepithelial cells [3,8]. Filaments are compartmentalized, the external or efferent side of a filament is differentiated from the inner or afferent side and the interlamellar region is positioned in-between.…”
Section: Introductionmentioning
confidence: 99%